2009
DOI: 10.1186/1476-069x-8-53
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: mechanistic considerations for associations between formaldehyde exposure and nasopharyngeal carcinoma

Abstract: Occupational exposure to formaldehyde has been linked to nasopharyngeal carcinoma. To date, mechanistic explanations for this association have primarily focused on formaldehyde-induced cytotoxicity, regenerative hyperplasia and DNA damage. However, recent studies broaden the potential mechanisms as it is now well established that formaldehyde dehydrogenase, identical to S-nitrosoglutathione reductase, is an important mediator of cGMP-independent nitric oxide signaling pathways. We have previously described mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Epstein-Barr virus (EBV) is implicated in the etiology of nasopharyngeal carcinoma (Marsh et al, 2007;Bosetti et al, 2008). Thompson and Grafstrom (2009) suggested that FA may exert an indirect influence in EBV reactivation through deregulation of nitrosothiol homeostasis and may also interact with the virus to promote epithelial cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is implicated in the etiology of nasopharyngeal carcinoma (Marsh et al, 2007;Bosetti et al, 2008). Thompson and Grafstrom (2009) suggested that FA may exert an indirect influence in EBV reactivation through deregulation of nitrosothiol homeostasis and may also interact with the virus to promote epithelial cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, reduced Adh7 expression has been implicated in oncogenesis and might influence viral life cycles through increased S-nitrosylation and formaldehyde-induced changes in cellular redox. 38,39 By contrast, the down-regulation of SGT proteins remarkably enhances the activity of HIV-1 virus. 40 An in-depth analysis of other down-regulated genes showed that most of them participated in 3 IFN-regulated pathways: JAK-STAT, p38 MAPK and PI3K.…”
Section: Antiviral Response Genesmentioning
confidence: 99%
“…Previous research has hypothesized that formaldehyde causes DNA damage that in turn results in cancer. 35 Epstein-Barr virus (EBV) infection and salted fish or food consumption are also risk factors of nasopharyngeal cancer. 36 For example, nasopharyngeal cancer in southern Chinese patients was found to be associated with the consumption of a salted fish containing nitrosamine, a known carcinogen.…”
Section: Discussionmentioning
confidence: 99%